Hydroxycinnamic and organic acids of snowdrops (Galanthus L.) - Dmitry Olegovich Bokov & , Aleksej Dmitrievich Malinkin, Irina Aleksandrovna Samylina, Vladimir Vladimirovich Bessonov (Journal of Applied Pharmaceutical Science, 2017)
The composition and content of hydroxycinnamic (HCA) and organic (OA) acids were investigated by HPLC with UV detection in Voronov’s snowdrop (Galanthus woronowii Losinsk.) and common snowdrop (Galanthus nivalis L.) crude herbal drugs. G. woronowii HCA composition is presented by neo chlorogenic, chlorogenic and cryptochlorogenic acids. Neo chlorogenic acid is absent in G. nivalis, but G. nivalis also contains chlorogenic and cryptochlorogenic acids. The total HCA content in G. woronowii was 84.1 ± 6.7 mg / 100 g, and in G. nivalis – 62.0 ± 5.0 mg / 100 g (0.06-0.08%). OA profile of two snowdrop species is presented by succinic, oxalic and malic acids. The total OA content in G. woronowii was 237.7 ± 2.4 mg / 100 g, and in G. nivalis – 405.1 ± 4.7 mg / 100 g (0.2-0.4%). The obtained data concerning minor specific biologically active substances composition can be used in the standardization and activity evaluation of drugs produced from snowdrops.
Keywords: Hydroxycinnamic acids, organic acids, Galanthus woronowii, Galanthus nivalis.